2022
DOI: 10.3389/fenvs.2022.940529
|View full text |Cite
|
Sign up to set email alerts
|

The Dilemma of Public Hearings in Land Expropriation in China Based on Farmers’ Satisfaction

Abstract: Although public hearings have been introduced into Chinese land expropriation as an important democratic supervision and conflict resolution mechanism for more than 15 years, there is a dearth of research into its qualities. Taking the farmers’ satisfaction with the public hearings as the critical quality indicator, this article analyzes the dilemma of this special institution in Chinese land expropriation. Process tracing is employed to analyze the design defect of the public hearing institution. Farmers’ sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…In the context of land acquisition negotiations, a sense of unfairness fuels conflicts [1]. Specifically, it is concluded that distorted procedure and inconsiderate arrangement affect procedural fairness [33]. Distribution fairness entails equitable compensation outcomes for farmers.…”
Section: Perceived Fairness In Farmersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of land acquisition negotiations, a sense of unfairness fuels conflicts [1]. Specifically, it is concluded that distorted procedure and inconsiderate arrangement affect procedural fairness [33]. Distribution fairness entails equitable compensation outcomes for farmers.…”
Section: Perceived Fairness In Farmersmentioning
confidence: 99%
“…Perceived procedural fairness directly influences farmers' attitude [20,37]. This complicates land acquisition negotiation [33]. Interestingly, there is not always an alignment between perceived fairness and the actual fairness level.…”
Section: Perceived Fairness In Farmersmentioning
confidence: 99%